BACTERIOLOGICAL ANALYSIS OF CATFISH (Clarias gariepinus) FROM EARTHEN AND CONCRETE PONDS OF A REPUTABLE FISH FARM IN MAKURDI, BENUE STATE, NIGERIA - Omeji, Samuel; A.A, GARBA,; J.A, ALO, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Bacteriological analysis of catfish (Clarias gariepinus) from earthen and concrete ponds of a reputable Fish Farm, Makudi, Benue State was investigated. The gills (7.8 × 106), Alimentary canal (8.2 × 106), fins (4.6 × 105) and skin (3.2 × 105) of C. gariepinus from earthen ponds had higher viable count than the gills (5.2 × 106) Alimentary canal (6.6 × 106), fins (2.3 × 105) and skin (2.6 × 105) of C. gariepinus from the concrete pond. Also coliform count of gills ((6.3 × 105) alimentary canal (6.7 × 105), fin (3.2 × 104) and skin (3.4 × 104) of C. gariepinus from earthen pond was higher than the coliform counts of gills (3.1 × 105), alimentary canals (3.6 × 104), fins (1.8 × 103) and skin (2.1 × 103) of C. gariepinus from concrete pond. Different species of bacteria with different shapes and morphology ranging from Staphylococcus sp, Escherichia coli, salmonella typhi, sligellasp, enterobactersp, klebsiellasp, psuedomonasssp, bacillus sp, to enterococcus faecalis were observed. These organisms were variously present in/on the different body parts of C. gariepinus from the earthen and concrete ponds. Of the various body parts of C. gariepinus from the concrete and earthen ponds, highest viable count (6.6 × 106) for C. gariepinus from the concrete and (8.2 × 106) from the earthen pond were recorded for alimentary canal while the lowest (2.3 × 105) for C. gariepinus from the concrete and (3.2 × 105) from the earthen pond were recorded for fins and skin, respectively. In addition, of the various body parts of C. gariepinus from the concrete and earthen ponds, highest coliform count (3.6 × 104) for C. gariepinus from the concrete and (6.7 × 105) from the earthen pond were recorded for alimentary canal while the lowest (2.3 × 105) from the concrete and (3.2 × 105) from the earthen pond were recorded for alimentary canal, however, the lowest coliform count (1.8 × 105) for C. gariepinus from the concrete and (3.2 × 104)from the earthen pond were recorded for fins, respectively. Generally, bacteria were more associated with C. gariepinus from the earthen pond than the concrete pond.